SOSIALISASI PENEGAKAN DAN KESADARAN HUKUM DALAM KONDISI PANDEMI MASYARAKAT DESA GIRIMUKTI KECAMATAN CIMARGA KABUPATEN LEBAK BANTEN - Ujang Hibar; Supandi Supandi; Anis Marsela; Mella Monika; Anggun Rahayuni; Afrida Tamariska (Indonesian Collaboration Journal of Community Services, 2021)
Girimukti Village is a village located in Cimarga district of Lebak Banten Regency with an area of about 529 hectares of population: 1140 KK with the number of RT: 22 and RW: 6. The environmental community of Girimukti Village is still not aware of the dangers of transmission and due to the Covid 19 virus which is very deadly, the community considers the disease a mediocre thing. The COVID-19 pandemic has not yet disappeared from our country. Various ways have been done by the government to overcome this outbreak, but also has not succeeded. Actually, if you want the government's efforts to succeed, then it should also be accompanied by community discipline to carry out health protocols that have been established by the government. COVID-19 successfully changes the habits we do every day both at home, at school, at work, on the street, and everywhere. We are made as helpless, because our movements are limited by COVID-19, thus making us unproductive which has an impact on the economic problems of families, communities, regions and countries. The central government until the regional government has issued several regulations in anticipation of the outbreak of the spread of the Corona-19 virus. At the lebak regency level, the Regent of Lebak has issued Lebak Regent Regulation No. 28 of 2010 on Guidelines for Adaptation of New Habits in the Condition of the Corona Virus Disease-19 Pandemic. Based on these things, the problems that will be examined in this study aim to: 1). Foster public legal awareness in pandemic situations, 2). Efforts to comply with health protocols in the community